Vaccinia virus in blood samples of humans, domestic and wild mammals in Brazil - Peres, Marina G. [UNESP]; Bacchiega, Thais S. [UNESP]; Appolinário, Camila M. [UNESP]; Vicente, Acácia F. [UNESP]; Mioni, Mateus de Souza Ribeiro [UNESP]; Ribeiro, Bruna L. D. [UNESP]; Fonseca, Clóvis R. S. [UNESP]; Pelícia, Vanessa C. [UNESP]; Ferreira, Fernando; Oliveira, Graziele P.; Abrahão, Jonatas S.; Megid, Jane [UNESP] (MDPI, 2018)
Outbreaks of Vaccinia virus (VACV) affecting cattle and humans have been reported in Brazil in the last 15 years, but the origin of outbreaks remains unknown. Although VACV DNA have been already detected in mice (Mus musculus), opossums (Didelphis albiventris) and dogs during VACV zoonotic outbreaks, no transmission to cattle or humans from any of these were reported during Brazilian outbreaks. In this work, we assessed the PCR positivity to VACV in blood samples of cows and other domestic mammals, wild rodents and other wild mammals, and humans from areas with or without VACV infection reports. Our results show the detection of VACV DNA in blood samples of cows, horse and opossums, raising important questions about VACV spread.
Keywords: Blood samples; Domestic mammals; Epidemiology; Humans; Public health; Transmission; Vaccinia virus; Wild mammals